PERUBAHAN KONDISI SOSIAL EKONOMI MASYARAKAT PASCA PEMBANGUNAN JEMBATAN SITI NURBAYA (Studi Kasus: Kelurahan Batang Arau Kecamatan Padang Selatan Kota Padang) - Dahnil, Dahnil; Prahara, Surya; Elfemi, Nilda (Pendidikan Sosiologi, 2014)
Thesis examines the socio-economic changes after the construction of the Bridge Siti Nurbaya (Case Study: Batang Arau Village Padang Selatan Urban District City of Padang), namely social interaction, social behavior and education as well as changes in livelihood and income levels. The goal is achieved in this study was to describe: